TOPONIM PADA MASA PEMERINTAHAN KESULTANAN PALEMBANG DARUSALLAM DI KECAMATAN ILIR TIMUR 1 PALEMBANG - Apriansyah, Refico; Zamhari, Ahmad Zamhari (Balai Arkeologi Sumatera Selatan, 2018)
East Ilir District I Palembang contains a wealth of historical and cultural data such ashistorical sites from the time of Sriwijaya to Colonial especially on toponymous studies. Thepurpose of this research is to know the value of toponym history during the reign of Sultanateof Palembang Darusallam in subdistrict of ilir east I Palembang. This study uses descriptivequalitative method is a method that talked about the results of observation interviewsor penelaan documents. This research is also systematically there are main activitiesysng done: Technique of data collection through activity of direct observation to researchlocation. From the research results can be concluded that the history of toponyms in EastIlir District I Palembang has a relationship with the history of the government of the Islamicempire in Palembang Palembang Sultanate Darusallam. The toponymous study in East Ilir IPalembang Sub-district is a lot of historical relics such as Kepandean Street (Iron Craft),Sayangan Street (Copper Craftsmen), Street Segaran (Swimming Baths), Tengkuruk RiverRoad (Son of Musi River), Angsoko Temple Road (Temple Complex and Tomb of PrinceMadi Angsoko of the kingdom of Palembang) as well as toponyms in the form of Nationalismand Geographical form (Natural Results).